2014
DOI: 10.1002/2014wr015597
|View full text |Cite
|
Sign up to set email alerts
|

Empirical assessment of theory for bankfull characteristics of alluvial channels

Abstract: We compiled a data set of 541 bankfull measurements of alluvial rivers (see supporting information) and used Bayesian linear regression to examine empirical and theoretical support for the hypothesis that alluvial channels adjust to a predictable condition of basal shear stress as a function of sediment transport mode. An empirical closure based on channel slope, bankfull channel depth, and median grain size is proposed and results in the scaling of bankfull Shields stress with the inverse square root of parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
134
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(147 citation statements)
references
References 39 publications
(74 reference statements)
12
134
1
Order By: Relevance
“…−1 * , and a similar result was found by Trampush et al (2014). Li et al (2015) concluded that the notion of a constant formative Shields stress for either gravel-or sand-bedded channels was not supported by the data.…”
Section: = 1220dsupporting
confidence: 67%
See 4 more Smart Citations
“…−1 * , and a similar result was found by Trampush et al (2014). Li et al (2015) concluded that the notion of a constant formative Shields stress for either gravel-or sand-bedded channels was not supported by the data.…”
Section: = 1220dsupporting
confidence: 67%
“…slope, or grain size (Lamb et al (2008); van Rijn (2016))) is explicitly accounted for. Moreover, while previous data compilations found that bankfull Shields stress increases systematically with decreasing grain size (Li et al (2015); Trampush et al (2014)), one may readily find data that contradict this trend. Channels formed by seepage erosion in sand (Devauchelle et al (2011)) are observed to transport sand as bedload and, like gravel bedload rivers, cluster approximately at the threshold of motion.…”
mentioning
confidence: 86%
See 3 more Smart Citations